Introducing data-driven learning on a PhD pre-sessional programme - Therova, Dana; Mckay, Andrew (Journal of Academic Language and Learning, 2022)
The aim of this article is to investigate the feasibility and benefits of a data-driven learning (DDL) approach in the context of an EAP pre-sessional programme at a UK university. It shows how self-compiled corpora can be usefully implemented on a pre-sessional programme to cater for the academic needs of international students in a multidisciplinary classroom. The participants were three international students preparing for a doctoral study by completing a ten-week online PhD pre-sessional programme. During the course, the students received training in the use of corpus software, which they utilised in regular weekly sessions to expand their discipline-specific knowledge. The usefulness and value of this approach was investigated through semi-structured interviews on completion of the programme. The results show that self-complied corpora can provide a valuable resource for writing in multidisciplinary EAP contexts. This paper thus argues that a DDL approach could be usefully implemented in mainstream EAP classes.